Dural Tears and Cerebrospinal Fluid Leak in Osteotomy Surgery for Ankylosing Spondylitis: Incidence, Risk Factors - Yue Huang; Fuze Liu; Yifei Li; Qi Zhu; Hai Wang; Jianguo Zhang (Orthopaedic Surgery)
ABSTRACT Objective The osteotomy surgery for ankylosing spondylitis (AS) presents a higher risk of dural injury and cerebrospinal fluid leakage compared to conventional spinal surgical procedures. However, there is currently a lack of systematic summaries in this field. This study aims to present the incidence and risk factors associated with dural tears and cerebrospinal fluid (CSF) leakage during corrective osteotomy procedures for AS with kyphotic deformity. Methods A retrospective analysis was conducted on patients diagnosed with AS in our hospital between June 2014 and May 2024 who presented with kyphotic deformity and underwent corrective osteotomy, specifically pedicle subtraction osteotomy (PSO) or Smith‐Petersen osteotomy (SPO). A total of 110 patients were included in this investigation. Among them, 98 patients underwent PSO (69 received single‐segment PSO; 29 received double‐segment PSO), while 12 patients underwent SPO. The mean age of the participants at the time of surgery was 36.25 years (ranging from 21 to 59 years). Of the total cohort, intraoperative dural tears occurred in 37 patients. Radiological parameters—including sagittal vertical axis (SVA), total kyphosis angle, posterior epidural space thickness at the PSO segment, sagittal alignment of the vertebral canal at the PSO segment, Andersson lesions, and dural ossification—were assessed using spine radiographs or computed tomography (CT) scans analyzed via Surgimap software. The continuous variables mentioned above were primarily compared between groups using independent samples t test, while categorical variables were mainly analyzed through the chi‐square test or Fisher's exact test for intergroup comparisons. Additionally, binary logistic regression was employed to further validate the risk factors associated with cerebrospinal fluid leakage in patients undergoing PSO osteotomy. Results The overall incidence of dural tears was found to be 33.6%. Specifically, the incidence during PSO procedures was recorded at 36.4%, whereas it was only 9.1% for SPO procedures. The upper lumbar PSO is the surgical segment with the highest probability of dural tears during PSO procedures. This study summarizes the imaging characteristics of patients undergoing PSO, revealing that those who experience dural tears and CSF leakage typically present with a smaller thickness of the epidural space at the osteotomy site and a higher prevalence of Andersson lesions and dural ossification. A multiple linear regression model indicates that reduced thickness of the epidural space at the osteotomy site, along with Andersson lesions and dural ossification, are significant risk factors for dural tears and CSF leakage following PSO surgery. Conclusion The total accidental dural tears rate in osteotomy surgery for AS is 33.6%. PSO presents a higher risk compared to SPO procedures. Factors such as the thickness of the posterior epidural space at the PSO segment, Anderson lesions, and dural ossification observed in CT scans serve as predictors for dural tears during PSO procedures. A comprehensive preoperative CT imaging assessment can provide valuable guidance regarding the potential occurrence of accidental dural tears and CSF leakage.